The Effectiveness of Motivational Interview (MI) in Academic Self-Handicapping in Senior High School’s Male Students - Hooshang Gravand; Saeid Sabziyan; Hosain Salimi (مطالعات روانشناسی تربیتی)
The aim of this study was performed to evaluating the effectiveness of motivational interview (MI) in reducing academic self-handicapping in senior high school’s male students in city bookan. This study was an experimental one with a pre-test, post-test and a control group. The statistical population includes all secondary high school male students in the city of bookan in the number of approximately 4150 people in the academic year 2013-2014 that 52 students selected by random multi-stage cluster sampling method and randomly assigned into two groups of experimental (n=26) and control group (n=26). The independent variable was the motivational interview training package based on Fields (2006) model, which was taught to the experimental group in 5 sessions for 90-minute were, while the control group followed its normal program. The instrument used in the study was Midgley self-handicapping Scale (2000). For analyzing data, univariate analysis of covariance (ANCOVA) were used. Findings from analysis of covariance showed the effectiveness of motivational interview on reducing academic self-handicapping (p <0.01). Based on the results of the current research, the MI reduces academic self-handicapping against students.